Physical Activity and Fitness
Healthy People 2010, Conference Edition, Chapter Physical Activity and Fitness Contents Goal Overview Issues and Trends Disparities Opportunities Interim Progress Toward Year 2000 Objectives Healthy People 2010—Summary of Objectives Healthy People 2010 Objectives Physical Activity in Adults Muscular Strength/Endurance and Flexibility Physical Activity in Children and Adolescents Access Related Objectives From Other Focus Areas Terminology References